2003
DOI: 10.1016/s1476-5586(03)80037-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Acidification Alters Lysosomal Trafficking in Human Breast Cancer Cells

Abstract: Cancer cells invade by secreting degradative enzymes, which are sequestered in lysosomal vesicles. In this study, the impact of an acidic extracellular environment on lysosome size, number, and distance from the nucleus in human mammary epithelial cells (HMECs) and breast cancer cells of different degrees of malignancy was characterized because the physiological microenvironment of tumors is frequently characterized by extracellular acidity. An acidic extracellular pH (pH(e)) resulted in a distinct shift of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
203
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(216 citation statements)
references
References 53 publications
10
203
0
3
Order By: Relevance
“…This effect was dose-dependent and not due to changes in the buffering capacity of the media or BA itself. The documented accumulation of acidic intracellular compartments is supportive of an affiliation with the media pH shift, by either contributing directly to the environmental acidification, or rather resulting from it, as seen in breast cancer cells (Glunde et al, 2003). Initially, we believed the upregulation of acidic vesicles reflected an increase in lysosome organelles, yet the LAMP-2 protein, expressed on lysosomal membranes in prostate tissue, decreased in expression ( Figure 4C) (Furuta et al, 1999).…”
Section: Accumulation Of Acidic Intracellular Vesiclesmentioning
confidence: 83%
“…This effect was dose-dependent and not due to changes in the buffering capacity of the media or BA itself. The documented accumulation of acidic intracellular compartments is supportive of an affiliation with the media pH shift, by either contributing directly to the environmental acidification, or rather resulting from it, as seen in breast cancer cells (Glunde et al, 2003). Initially, we believed the upregulation of acidic vesicles reflected an increase in lysosome organelles, yet the LAMP-2 protein, expressed on lysosomal membranes in prostate tissue, decreased in expression ( Figure 4C) (Furuta et al, 1999).…”
Section: Accumulation Of Acidic Intracellular Vesiclesmentioning
confidence: 83%
“…Also, MMP9 gene expression was correlated with invasion assays results. Previous studies demonstrated that the expression of genes involved in metastasis such as MMP-9 and cathapsin B increases at the acidic condition in the tumor tissue [6,7,26,[29][30][31][32]. Cathepsin L also amplifies the proteinase cascade through the activation of urokinase-type plasminogen activator (uPA) which is critical for metastatic cascade in tumor cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 plays a vital role in promoting tumor invasion and tissue remodeling, and participates in the release of cell surface precursorform of many growth factors by proteolysis of several ECM components [2,[29][30][31]. Glunde et al (2003) reported filopodia formation which was observed more frequently in highly metastatic breast cancer cells maintained in acidic pH [32]. Raymond et al (2008) reported that the acidosis promotes more invasive phenotypes of melanoma cells in vitro and in vivo [29].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of V-ATPases with bafilomycin or through siRNA silencing prevented peripheral localization of Rab27 secretory vesicles and blocked heat shock protein 90␣ secretion (41). Inhibiting V-ATPases may prevent peripheral localization of molecules indirectly because low extracellular pH induces a redistribution of lysosomes toward the cell periphery (42).…”
Section: Discussionmentioning
confidence: 99%